The Specificity of the First Cognitive Acts in Realist Metaphysics as interpreted by Mieczysław A. Krąpiec and Stanisław Kamiński - Paweł Gondek (Studia Gilsoniana)
The issue of the first cognitive acts is a decisive factor in the adopted methods of philosophical explanation of reality. The concept of the first cognitive acts presented in this article was developed by M. A. Krąpiec and S. Kamiński within the framework of realist metaphysics. They methodologically elaborated the problem of the primordial metaphysical experience, which constitutes a direct and assumption-free reference to existing things. The interpretative difficulties that arise in this area result from the need to engage pre-scientific sources of cognition at the starting point. Simultaneously, the value of this cognition is emphasized in the aspect of affirming the existence of something beyond the subject, which is expressed through the existential judgment and constitutes a preconception of the proper object of philosophy. In this conception, the first cognitive acts are accepted with appropriate refinement. This includes the dialectical method, which allows for a justified transition from pre-scientific cognitive results to preliminary philosophical assertions about reality. Subsequently, the intuitive-reductive method is introduced, in which, for a specified effectual state, we indicate the sole and ultimate ontic cause. In this method, the context of states of affairs constitutes a necessary condition for accepting theses. On such foundations, in realist metaphysics, one moves from the first cognitive acts to the formulation of systematic theses.